Phenomenology of Mothers’ Lived Experiences of Raising Children with Autism and Study of the Legal Status of Social Protections for Mothers of Certain Children - Mehrabi, Mahbobeh; Amiri, Abtin (International Journal of Education and Cognitive Sciences, 2022)
Purpose: This study aimed to explore the lived experiences of mothers raising daughters with autism spectrum disorder (ASD).Methods and Materials: A qualitative research design based on descriptive-interpretive phenomenology was employed. Twelve mothers of autistic daughters were purposefully selected from occupational therapy centers in Bandar Abbas. Data were collected through in-depth semi-structured interviews, each lasting between 45 to 70 minutes. Interviews were audio-recorded, transcribed verbatim, and analyzed thematically to identify recurring patterns and core experiential themes. Ethical protocols, including informed consent and confidentiality, were rigorously observed throughout the research process.Findings: Analysis revealed five major themes: (1) the burden of ongoing and challenging caregiving, (2) conflicting emotional experiences, (3) search for social support, (4) redefinition of motherhood, and (5) persistent anxiety about the child’s future. Mothers described caregiving as physically exhausting and emotionally draining, with frequent episodes of unpredictability and public misunderstanding. Emotional experiences ranged from guilt and despair to deep love and spiritual acceptance. Social isolation and stigma were recurrent, though even minimal instances of support were found to be deeply impactful. Mothers reported significant transformations in how they understood and enacted their maternal roles, shifting from normative expectations to more flexible and emotionally attuned identities. A common and profound concern was the uncertainty surrounding their daughters’ futures in the absence of sustained social and institutional care.Conclusion:. Interventions must address not only the needs of autistic children but also the emotional, informational, and structural support required by their mothers. Policy and practice should prioritize culturally sensitive, gender-informed caregiving frameworks to improve maternal well-being and caregiving outcomes.